LEGAL OPINI ATAS PUTUSAN PENGADILAN TINDAK PIDANA KORUPSI PADA PENGADILAN NEGERI MEDAN NOMOR 13/PID.SUS-TPK/2018/PN MEDAN, TANGGAL 19 APRIL - Gultom, Maidin (Fiat Iustitia : Jurnal Hukum, 2020)
Article 12 a PTPK Law only applies to State Employees and State Administrators. Article 12 a PTPK Law basically regulates the actions of civil servants or state administrators that are contrary to their duties or obligations. The convict Sujendi Tarsono alias Ayen is not a Civil Servant or a State Administrator. The person concerned is as an entrepreneur as Director of PT Ada Mobil / Owner Ada Jadi Mobil. In connection with the description above, the possibility that occurs is the occurrence of errors in persona and Error in Objecto, meaning that the wrong person and the wrong object that was decided to convict Sujendi alias Ayen. In my opinion, the defendant SUJENDI TARSONO alias AYEN can be categorized as Also Participating in this case Telling Doing (Middelijk daders). Forcing to do is someone who wishes to do something criminal, but does not do it himself, but rather tells others to do it. The person who ordered it uses someone else (ie the person who was told) to realize his intention. The main requirement (characteristic) of ordering to do is that the person who is told to be must be a person who cannot be accounted for legally (according to Criminal Law). The reasons are as follows: a. Because of criminal exemptions. b. Because one element of the crime was not fulfilled, for example the element of error (intentional), which is related to the intention (as a subjective element) in the occurrence of the crime. Those who do what is wrong (menrea) while those who do have no mistakes. The liability of the person who ordered it to do is limited to the act carried out by the material maker (the person ordered).